Língua portuguesa: um pretexto para o exercício do ser em liberdade - Ferreira, Sueli da Costa (1992)
The study concerns the importance of the students autoknowledge for the sake of self-achievement. It deals with the presentation of a teaching experience which was developed in five high junior schools in Rio de Janeiro Country with teenagers students. Theoretical support is based on philosophical and educational concepts which come not only from humanism and existencialism but psycho-didactical pressupositions as well as specifically lead to the teaching centralized in the student, according to Carl Rogers learning theory.The analysis of the subjects’opinions - the teenagers students - reveals the way on how the worting skill in Portuguese Language becomes a good and pleasant self exercise - when the students have freedom to create. It also shows us that not always "a pattern failure" means "a content failure". In truth, as the students are led to learn in liberty they will be able to think and write with coherence and criativity.